The SDGs Will Require Integrated Agriculture, Nutrition, and Health at the Community Level. (March 2016) - Canavan, Chelsey R.; Graybill, Lauren; Fawzi, Wafaie; Kinabo, Joyce
Child malnutrition is an urgent and complex issue and requires integrated approaches across agriculture, nutrition, and health. This issue has gained prominence at the global level. While national-level efforts are underway in many countries, there is little information on how to integrate at the community level. Here, we offer a community-based approach using cadres of agricultural and community health workers, drawing on qualitative work we have conducted in Tanzania. Agriculture is an important driver of nutritional and health outcomes, and improving child health will require practical solutions for integration that can add to the evidence base.